HOW UNCERTAINTY STIMULATES OVER-HARVESTING IN A RESOURCE DILEMMA: THREE PROCESS EXPLANATIONS - JAGER, WANDER; JANSSEN, MARCO A.; VLEK, CHARLES A.J. (Journal of environmental psychology, 2002)
We report on a series of computer simulation experiments regarding the management of a common resource. We were particularly interested in the effects of uncertainty and satisfaction on the harvesting behaviour of simulated agents. The experimental study of long-term dynamics of threatened resources can hardly be carried out using human subjects. We therefore experimented with simulated consumers, the so-called consumats, whose properties are derived from a comprehensive, multitheoretical model of consumer behaviour. A consumat is equipped with needs and abilities, and may engage in different cognitive processes, such as deliberation, social comparison, imitation, and repetition of previous behaviour. In a first simulation experiment we show as to how uncertainty may stimulate an imitation effect that promotes over-harvesting. In two subsequent series of experiments, we show that increased uncertainty results in an increased ‘optimism’ of consumats regarding future outcomes, an increased likelihood of imitative behaviour, and a lesser adaptation of harvesting behaviour during resource depletion. These ‘process-effects’ promote higher levels of harvesting from a collective resource. The main experimental conclusions and the issue of validating simulation results are discussed.